PENGARUH KOMPETENSI, PEMANFAATAN TEKNOLOGI INFORMASI, SISTEM PENGENDALIAN INTERN PEMERINTAH, KOMITMEN APARATUR DESA DAN PENGELOLAAN LINGKUNGAN TERHADAP PENGELOLAAN KEUANGAN DANA DESA DI KECAMATAN RANGSANG BARAT KABUPATEN KEPULAUAN MERANTI - Kenari, Purnama; Enni, Savitri; Julita, Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to analyze the Competence, Utilization of Information Technology, Government Internal Control Systems, Village Apparatus Commitment and Environmental Management to Village Fund Financial Management. The population of this research was 12 villages in West Rangsang sub-district. The selection of research samples using purposive sampling method. The sample in this study was the village head, the village secretary, the head of financial affairs, the head of administrative and planning affairs, as well as the village consultative body with 60 respondents. The data analysis used is multiple regression analysis. The results showed that the Competence, Utilization of Information Technology, Government Internal Control Systems and Environmental Management influenced the Village Fund Financial Management. Meanwhile, Village Apparatus Commitment has no effect on Village Fund Financial Management.Keywords: Village Fund Management, Competence, Utilization of Information Technology, SPIP, Commitment, Environmental Management